Complement Initiation Varies by Sex in Intestinal Ischemia Reperfusion Injury - Wu, Miaomiao; Rowe, Jennifer M.; Fleming, Sherry D. (Frontiers in Immunology, 2021)
Intestinal ischemia reperfusion (IR)-induced tissue injury represents an acute inflammatory response with significant morbidity and mortality. The mechanism of IR-induced injury is not fully elucidated, but recent studies suggest a critical role for complement activation and for differences between sexes. To test the hypothesis that complement initiation differs by sex in intestinal IR, we performed surgical intestinal IR on male and female WT C57BL/6, C1q-/-, MBL-/-, properdin (P)-/- mice. Initial studies demonstrated a difference in complement mRNA and protein in male and female WT mice. To further investigate the differences, WT, C1q-/- MBL-/- and P-/- male and female mice were subjected to intestinal IR followed by analysis of intestinal injury, C3b and C5a production and ex vivo secretions. In response to IR, both C1q and MBL expression and deposition in increased WT male mice, while only MBL expression and deposition increased in WT female mice. These data suggested that males use both C1q and MBL pathways, while females tend to depend on lectin pathway during intestinal IR. Subsequently, C1q-/- and MBL-/- male mice attenuated tissue damage, and decreased ex vivo generation of PGE2. However, females attenuated injury in MBL-/- but not C1q-/- mice. In addition, all female mice produced significant LTB4 with limited PGE2. Both sexes produced significantly less serum C5a in MBL-/- and P-/- mice. Our findings suggested that complement activation induced in intestinal IR in a sex-dependent manner.